Physical and feasible: Climate change adaptation in Longyearbyen, Svalbard - Alexandra Meyer (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna) (Polar Record, 2022)
The abstract is available here: https://uscholar.univie.ac.at/o:1630989 The abstract is available here: https://uscholar.univie.ac.at/o:1630989